Investigation of Novel Aronia Bioactive Fraction-Alginic Acid Nanocomplex on the Enhanced Modulation of Neuroinflammation and Inhibition of Aβ Aggregation - Jang, Bong Keun; Shin, Soo Jung; Park, Hyun Ha; Kumar, Vijay; Park, Yong Ho; Kim, Jeom Yong; Kang, Hye Yeon; Park, Sunyoung; Kwon, Youngsun; Shin, Sang Eun; Moon, Minho; Lee, Beom Jin (Pharmaceutics, 2025)
Background/Objectives: Aronia extract or its active compounds, especially anthocyanin, have shown potential for Alzheimer’s disease (AD)-related pathologies, including neuroinflammation, fibrillogenesis of amyloid beta (Aβ), and cognitive impairment. However, there was still concern about their structural instability in vivo and in vitro. To solve the instability of anthocyanins, we combined aronia bioactive factions (ABFs) and alginic acid via electrostatic molecular interactions and created an ABF–alginic acid nanocomplex (AANCP). We evaluated whether it is more stable and effective in cognitive disorder mice and neuroinflammation cell models. Methods: The physicochemical properties of the AANCP, such as nanoparticle size, structural stability, and release rate, were characterized. The AANCP was administered to scopolamine-injected Balb/c mice, and to BV2 microglia treated with lipopolysaccharide (LPS) and amyloid beta (Aβ). Inflammation responses were measured via qPCR and ELISA in vitro, and cognitive functions were measured via behavior tests in vivo. Results: The AANCP readily formed nanoparticles, 209.6 nm in size, with a negatively charged zeta potential. The AANCP exhibited better stability in four plasma samples (human, dog, rat, and mouse) and was slowly released in different pH conditions (pH 2.0, 7.4, and 8.0) compared with non-complexedABF. In vitro studies on microglial cells treated with AANCPs revealed a suppression of inflammatory cytokines (tumor necrosis factor-alpha and interleukin-6) induced by LPS. The AANCP increased microglial Aβ phagocytosis through the activation of triggering receptor expressed on myeloid cell 2 (TREM2)-related microglial polarization. The AANCP inhibited aggregation of Aβ in vitro and alleviated cognitive impairment in a scopolamine-induced in vivo dementia mouse model. Conclusions: Our data indicate that AANCPs are more stable than ABFs and effective for cognitive disorders and neuroinflammation via modulation of M2 microglial polarization.
Keywords: anthocyanin; aronia bioactive fraction–alginic acid nanocomplex; electrostatic interaction; enhanced stability; nanoparticles; neuroinflammation; reduced aβ aggregation